Altered sensory integration from body and language development in children with autism spectrum disorder. Issue 4 (14th December 2022) - Yoshimura, Yuko; Hasegawa, Chiaki; Tanaka, Sanae; Ikeda, Takashi; Yaoi, Ken; Iwasaki, Sumie; An, Kyung‐min; Kikuchi, Mitsuru
Abstract: Aim: Although atypical sensory motor processing has been investigated in children with autism spectrum disorder (ASD), whether or not atypical sensory motor processing is related to altered language function in children with ASD remains unclear. Methods: This study examined the relationship between sensory motor processing and language conceptual inference ability in 3–10‐year‐old children with ( n = 61) and without ( n = 114) ASD. Language performance was assessed using the language conceptual inference task of the Kaufman Assessment Battery for Children (K‐ABC). Sensory processing was assessed using the Caregiver Sensory Profile. Results: In children with ASD, altered processing of the fine motor/perceptual factor scored by sensory profile was found to be significantly related to language conceptual inference ability in the K‐ABC, representing the integrated abilities of language comprehension and language expression, which reflect language semantic concept formation. Conclusions: For children with ASD, the results suggest a relationship between difficulties of integrating sensory information perceived from the body adjusting fine movement and deficiencies of language semantic conceptual formation. Abstract : The current study was aimed at examining the relationship between the sensory processing characteristics and language conceptual inference ability in 3–10‐year‐old children with autism spectrum disorder (ASD). Significant and negative correlation was found between the factor of fine motor/perceptual in the caregiver sensory profile and language ability in children with ASD. Our study suggests that the sensory motor system is involved in early language concept formation and semantic memory in children with ASD without intellectual disabilities.